2005
DOI: 10.1002/lt.20458
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of a single bolus administration of recombinant factor VIIa in liver transplantation due to chronic liver disease

Abstract: Orthotopic liver transplantation (OLT) can be associated with excessive blood loss. As a result, there may be increased risk of adverse outcomes. Activated recombinant factor VII (rFVIIa) has demonstrated the ability to improve hemostasis in a variety of disorders; however, there has been a limited amount of research into its use in OLT. The purpose of this dose-finding study was to examine the efficacy and safety of rFVIIa in the reduction of bleeding in patients undergoing OLT. In this doubleblind trial, pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
161
2
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(175 citation statements)
references
References 21 publications
8
161
2
4
Order By: Relevance
“…Previous observations are in line with the long lasting evidence that the PT is a poor predictor of peri-or post-operative bleeding in cirrhosis [15][16][17][18][19][20][21][22]. Furthermore, a powerful pro-hemostatic agent, such as recombinant activated factor VII (rFVIIa), although capable of considerably shortening the PT [23], proved to be ineffective to stop esophageal bleeding [23,24], or to reduce bleeding at surgery [25,26].…”
Section: Prothrombin Timementioning
confidence: 63%
“…Previous observations are in line with the long lasting evidence that the PT is a poor predictor of peri-or post-operative bleeding in cirrhosis [15][16][17][18][19][20][21][22]. Furthermore, a powerful pro-hemostatic agent, such as recombinant activated factor VII (rFVIIa), although capable of considerably shortening the PT [23], proved to be ineffective to stop esophageal bleeding [23,24], or to reduce bleeding at surgery [25,26].…”
Section: Prothrombin Timementioning
confidence: 63%
“…17,20 In these studies rFVIIa was not associated with thromboembolic complications, but the number of such events was small, limiting the likelihood of finding such differences if they in fact were present.…”
Section: Rationalementioning
confidence: 90%
“…66 Clinical trials of rFVIIa in the treatment of active bleeding in liver transplantation have used doses ranging from 20-120 g/kg/dose on varying schedules. [67][68][69][70] The clinical efficacy of rFVIIa in the treatment of cirrhotic patients with variceal bleeding has been studied in 2 randomized, doubleblinded trials by Bosch et al, which showed no overall effect of rFVIIa versus placebo and no significant differences in reported mortality, incidence of adverse events, or treatment failure. 71,72 In the earlier trial, post hoc analysis of rFVIIa in patients with moderate to severe cirrhosis (Child-Pugh class B and C) and variceal bleeding showed a significant decrease in the number of patients in whom this failed to control the bleeding.…”
Section: Rfviia and Prothrombin Complex Concentratesmentioning
confidence: 99%
“…None showed any difference in mortality or thromboembolic adverse events (TAEs), and only one study showed a benefit of rFVIIa on decreasing RBC transfusion requirements. [66][67][68][69][70] Whereas rFVIIa has rarely been associated with TAEs when used for labeled indications, there has been concern with increased rates of TAEs with off-label use. A meta-analysis by Hsia et al of TAE rates across 22 clinical trials for various indications revealed a statistically significant increase in arterial thromboembolism, with a 4.5% rate in the rFVIIa-treated patients and a 2% rate with placebo.…”
Section: Rfviia and Prothrombin Complex Concentratesmentioning
confidence: 99%